Scuba diving new attraction for UMP students - Siti Rabiatull Aisha, Idris (2020)
Pulau Perhentian, 24 July 2020 - A new experience awaits students who are interested in scuba diving activities when it was introduced as the latest activity organised by the Co-Curriculum Centre of Universiti Malaysia Pahang (UMP).